First reported case of Simpson–Golabi–Behmel syndrome in a female fetus diagnosed prenatally with chromosomal microarray. Issue 5 (17th March 2017) - Støve, Heidi Kristine; Becher, Naja; Gjørup, Vibike; Ramsing, Mette; Vogel, Ida; Vestergaard, Else Marie
Key Clinical Message: Simpson–Golabi–Behmel syndrome (SGBS) is a rare X‐linked syndrome. Female carriers may have mild manifestations. Macrosomia, polyhydramnios, and kidney and urinary tract anomalies are common findings in male fetuses. We present the first case of a severely affected female fetus with stigmata of SGBS and a deletion involving the GPC3 gene. Abstract : Simpson–Golabi–Behmel syndrome (SGBS) is a rare X‐linked syndrome. Female carriers may have mild manifestations. Macrosomia, polyhydramnios, and kidney and urinary tract anomalies are common findings in male fetuses. We present the first case of a severely affected female fetus with stigmata of SGBS and a deletion involving the GPC3 gene.